Evaluation and analysis of an enhanced hybrid wireless mesh protocol for vehicular adhoc network - Eltahir, Amal A.; Saeed, Rashid Abdelhaleem; Mukherjee, Amitava; Hasan, Mohammad Kamrul (Springer Open, 2016)
This paper presents a new clustering mechanism for the multi-hop relay in vehicular communication. In the proposed mechanism, the cluster-head selection is implemented using the enhanced hybrid wireless mesh protocol (E-HWMP) protocol, which is based on the IEEE802.11p and IEEE802.11s standards. Then, multi-hop routing is designed for VANET in Wireless Mesh Networks (WMNs). Therefore, the main aim of this study is to enhance the integration of VANET with a cellular network (i.e., LTE). As a result, the coverage can be extended. The proposed E-HWMP mechanism is evaluated by the NS2 simulator, and the VanetMobiSim is used as a mobility generator. The proposed E-HWMP mechanism is compared to the existing mechanism based on the packet’s delivery ratio, packet loss, throughput, overhead, and average end-to-end delay. The results demonstrate that the proposed E-HWMP mechanism outperforms the existing clustering mechanism.